The shot described - Ball, K. (coachesinfo.com)
One of the most important skills in water polo is the shot for goal. Good mechanics of the shot is of paramount importance to the polo player to optimize ball speed as well as to increase consistency and accuracy. Sound mechanics also decreases the chance of injury from repeated throwing at high speed or from a technique that puts excessive strain on a particular part of the body such as the shoulder or elbow. This article focuses on the basic shot used in field and penalty settings. Content: - Introduction - Key Points -The Shot for Goal: Start position - Follow through